Made you look - Grant, Tanya (Berkley, 2025)
"A Catskills retreat turns deadly for a group of influencers when a snowstorm cuts them off from their greatest resource--their followers--just as a killer strikes in this irresistible debut thriller. Sydney Kent is the ultimate It Girl. You want her effortless style, her charisma, her hair. You want to be her; you want to be with her. But the trouble with a star is that everyone else looks dull in comparison. Despite Caitlyn's social media cunning, it's impossible for her to step out from Sydney's shadow. Even Lucy, Sydney's best friend since before her fame, can't escape her role as full-time photographer to the influencer. When the women are invited to post content for a secluded new retreat in the Catskills, alongside Sydney's boyfriend Jeff, stylist Nash, and manager Brent, the weekend feels like it will be a fresh start. But an unexpected snowstorm traps the group together with no cell service, no Wi-Fi, and no way out. Then a killer strikes, and the dream trip becomes a nightmare. Secrets, lies, and scandals are forced to the surface, and the friends can't help but suspect the murderer might be among them. Worse, the killing has only just begun. But where there's danger, there's juicy, jaw-dropping, name-making content to be created. You know you want to look"-- Provided by publisher.